GREEN MARKETING STRATEGIES AS A COMPETITIVE ADVANTAGE FOR SMALL AND MEDIUM ENTERPRISES (SMES) - Sari Handayani; Siti Nur Soleha; Ahmad Zainuddin; Yosa Endriatmoko (CV. Adiba Aisha Amira, 2025)
Environmental sustainability issues have become a global concern affecting business practices across various sectors, including Small and Medium Enterprises (SMEs). This research aims to examine green marketing strategies as one approach that can provide a competitive advantage for SMEs in facing modern market competition. The method used is a literature review, analyzing various scientific references from relevant journals, books, and research reports published in the last ten years. The study results indicate that applying green marketing principles, such as eco-friendly products, sustainable pricing, efficient distribution, and environmental value-based promotion, can enhance brand image, consumer loyalty, and product differentiation. Despite the challenges faced by SMEs, such as limited resources and knowledge, this strategy can still be implemented through a phased and innovative approach. The conclusion of this study emphasizes that green marketing is not only a response to environmental trends, but also a strategic foundation for building sustainable competitive advantages for SMEs.